ANALISA KEBUTUHAN AIR BERSIH DI KAWASAN PERMUKIMAN DESA BLANG KOLAK I KECAMATAN BEBESEN KABUPATEN ACEH TENGAH - Shinta, Noviana; Sembiring, Rahmad Dian; Pinem, Dessy Eresina (LPPM ISTP, 2023)
Clean water is a very serious problem in Blang Kolak I Village. As the population increases every year, the need for clean water continues to increase, while water availability is still limited. The current source of clean water in Blang Kolak I Village is PDAM water and community well water. In this research, two research methods were used, namely descriptive research methods and quantitative research methods. The analysis used is a descriptive analysis of clean water problems, population projections, availability and need for clean water and solutions to meet clean water needs. From the results of the analysis carried out, it can be seen that the total need for clean water according to the minimum service standards of the Directorate General of Human Settlements and Public Works in 1996, in the initial year was 5.45 liters/second and in 2028 (10 year projection) it was 6.58 liters/second. The clean water needed is 70 liters/person/day while the current water availability is 28 liters/person/day. Solutions to fulfill clean water needs that can be applied at the research location to fulfill clean water needs are by utilizing community well water (shallow wells), improving the management of Regional Drinking Water Companies (PDAM) and deep well pumps.